University teachers’ focus on students: Examining the relationships between visual attention, conceptions of teaching and pedagogical training - Murtonen Mari; Anto Erkki; Laakkonen Eero; Vilppu Henna (European Association for Research on Learning and Instruction EARLI, 2025)
Teachers’ focus on their students’ learning is considered central in high-quality university teaching. This frontline research introduces a novel way to study how focusing on students’ learning can be found on the level of teachers’ visual noticing combined with verbal interpretations, i.e. their professional vision, when they observe teaching situations. A central question is also, whether professional vision skills are connected to teachers’ pedagogical education. Two short videos depicting teaching during a lecture, including different types of trigger events, were presented to teachers (N = 49), who were asked to think aloud while watching, and numerically evaluate the success of the teaching, to reveal their interpretation of the teaching situation. The results showed that pedagogically trained teachers paid more visual attention on the students and less on the teacher. Visual noticing of critical incidents preceded the formulation of accurate verbal interpretations. Noticing that the students were not active was connected to learning facilitating conceptions, which were further connected with corresponding numerical evaluation of the successfulness of teaching. Teachers who visually notice the important incidents during teaching can also formulate a more accurate verbal interpretation of the situation. Contrary to studies at lower levels of education, our study did not found evidence on the connection between teaching experience and professional vision. At the university level, pedagogical education seems to be a stronger predictor of professional vision.